Cleavage : men, women, and the space between us - Boylan, Jennifer Finney, 1958- (Celadon Books, 2025)
"What is the difference between men and women? Jennifer Finney Boylan, bestselling author of She's Not There and co-author of Mad Honey with Jodi Picoult, examines the divisions-as well as the common ground-between the genders, and reflects on her own experiences, both difficult and joyful, as a transgender American. Jennifer Finney Boylan's She's Not There was the first bestselling work written by a transgender American. Since its publication twenty years ago, she has become the go-to person for insight into the impact of gender on our lives, from the food we eat to the dreams we dream, both for ourselves and for our children. But Cleavage is more than a deep dive into gender identity; it's also a look at the difference between coming out as trans in 2000-when many people reacted to Boylan's transition with love-and the present era of blowback and fear. How does gender affect our sense of self? Our body image? The passage of time? The friends we lose-and keep? Boylan considers her womanhood, reflects on the boys and men who shaped her, and reconceives of herself as a writer, activist, parent, and spouse. With heart-wrenching honesty, she illustrates the feeling of liminality that followed her to adulthood, but demonstrates the redemptive power of love through it all. With Boylan's trademark humor and poignancy, Cleavage is a sharp, witty, and captivating look at the triumphs and losses of a life lived in two genders. Cleavage provides hope for a future in which we all have the freedom to live joyfully as men, as women, and in the space between us"--